Taḥlîl al-Akhṭo’ al-Kalâmiyyah wa Mu’âlajatuha li Tarqiyyah Ta’lîm al-Lughah al Arabiyyah - Muhammad Fachruddin Fadhli Dzikri; Inayatur Rahman; Uril Bahruddin (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose- The purpose of this study is to find the location of errors in students' Arabic speaking skills and then overcome these errors with the error analysis method, and this research focuses more specifically on showing the analysis of verbal errors. Design/Methodology/Approach- The method used in this research is descriptive qualitative, data obtained from interviews, observations, and documentation at the Pondok Pesantren Nurul Jadid Probolinggo. This study used a sample of 7th grade students with a total of 30 students. Findings— During the process of learning Arabic, especially speaking Arabic skills, students are not able to distinguish and pronounce the sounds of Arabic letters properly and correctly. This causes phonemic errors that occur in the students of the Nurul Jadid Probolinggo Islamic Boarding School during the Arabic learning process. There are many phonetic errors that are often found in speaking Arabic, including errors in pronouncing the letters. Arabic has long vowels and consonants that other languages ​​like Indonesian don't have. There are even sounds that are close together and sounds that are firm are characteristics of Arabic which are often problematic in learning Arabic. Research Limitation/Implications- Therefore the author divides from the mistakes made by the students to overcome them. This research could not be deeper because of the limited time given, even so this research got satisfactory results and it is hoped that it can help develop the maharah kalam learning process at the Nurul Jadid Islamic Boarding School Probolinggo.